FGB, TNFα, IL-1β, LPL, ITGB3, and TGFB1 genes polymorphism in patients with recurrent myocardial infarction - S. D. Mayanskaya; L. A. Garaeva; A. T. Teplyakov; M. L. Filipenko; E. A. Sokolova; O. A. Kravtsova; E. V. Berezikova (Бюллетень сибирской медицины, 2021)
The aim. To evaluate the association of fibrinogen (FGB), tumor necrosis factor α (TNFα), interleukin 1β (IL-1β), lipoprotein lipase (LPL), platelet glycoprotein (ITGB3), and transforming growth factor β (TGFB1) genes  with the incidence of recurrent myocardial infarction (MI) in patients living in the middle Volga region.Materials and methods. The study included 104 people with recurrent MI compared to 280 people who had just one episode of MI. TNFα (rs1800629), IL1B (rs16944), TGFB1b (rs1800469), FGB (rs1800788), ITGB3 (rs5918) and LPL (rs328) gene polymorphism was determined in all patients using competing TaqMan probes. Association estimation was performed with multivariate logistic regression analysis.Results. Patients with recurrent MI much more often had TNFα, IL1B, TGFB1b, FGB, ITGB3 and LPL allele and genotype polymorphism. Moreover the risk of MI increased significantly in a case of combination of FGB (alleles and genotypes) and TNFα (alleles and genotypes) gene polymorphisms (OR = 4.04, 95% CI = (1.895–8.615), p = 0.0001).Conclusion. Thus, FGB, LPL, TNFα, TGFB1b and ITGB3 gene polymorphism are associated with more severe coronary heart disease and may be a risk factor of recurrent MI development. The dominant total contribution of the FGB (rs1800788) and TNFα (rs1800629) polymorphic genes to the development of recurrent MI in the population of the middle Volga region was revealed.